Pengaruh Citra Merek Dan Kualitas Produk Terhadap Kepuasan Konsumen Sepatu Sepakbola Nike di Jakarta Timur - Wou, Wilfridus; Iskandar, Donant Alananto (Research and Community Service UNIVERSITAS KALBIS, 2023)
This study aimst determine whether there is an influence between Brand Image and Product Quality on Consumer Satisfaction of Nike soccer shoes in East Jakarta. This study uses aquantitative method approach through a surveyy of 130 Nike soccer shoes users. The sampling method is non-probability sampling with purposive sampling type with the number of respondents 130 respondents,the data collection technique is a questionnaire. Thedata processing method uses linear regression analysis with the help of SPSS version 25 program. The results of this study conclude that Brand Image and Product Quality have a simultaneous and significant effect on Consumer Satisfaction.